2019
DOI: 10.1002/bjs.11299
|View full text |Cite
|
Sign up to set email alerts
|

Population-based study of the effect of preoperative breast MRI on the surgical management of ductal carcinoma in situ

Abstract: Background Determinants of the use of breast MRI in patients with ductal carcinoma in situ (DCIS) in the Netherlands were studied, and whether using MRI influenced the rates of positive resection margins and mastectomies. Methods All women aged less than 75 years, and diagnosed with DCIS between 2011 and 2015, were identified from the Netherlands Cancer Registry. Multivariable logistic regression analyses were performed, adjusting for incidence year, age, hospital type, DCIS grade and multifocality. Results Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…We found that MRI did not result in higher mastectomy rates, which is in line with some studies that also reported no effect of MRI on mastectomy rates [21,23]. By contrast, the majority of the studies on the effect of MRI on mastectomy rates reported an increased rate [8,20,22,24,26]. Differences between these studies are hard to explain but are probably related to the radiologists' interpretations of the MRI images.…”
Section: Discussionsupporting
confidence: 88%
“…We found that MRI did not result in higher mastectomy rates, which is in line with some studies that also reported no effect of MRI on mastectomy rates [21,23]. By contrast, the majority of the studies on the effect of MRI on mastectomy rates reported an increased rate [8,20,22,24,26]. Differences between these studies are hard to explain but are probably related to the radiologists' interpretations of the MRI images.…”
Section: Discussionsupporting
confidence: 88%
“…Three studies were RCTs [19][20][21], 18 were comparative cohorts [11,12,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and five were single arm cohorts [12,21,[37][38][39], with a total of 20,415 patients (260 from the RCTs and 20,155 from the observational studies). Most studies were conducted in the USA or in the Netherlands.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the 18 comparative cohorts included [11,12,[22][23][24][25][26][27][28][29][30][31][32][33][34], 16 were retrospective analyses of medical records or population registries [11,12,[22][23][24][25][26][27][29][30][31][32][33][34][35][36], three of them comparing different time periods (pre-and post-implementation of MRI) [23,24,26]. Three cohort studies had larger sample sizes, one used the Breast Cancer Surveillance Consortium registry data with 2437 patients with DCIS from 2010 to 2014 [27], another study included data of 2319 patients from a cancer centre in New York (USA) from 1997 to 2010 [28] and the last study used the Netherlands Cancer Registry (NCR) including 10,415 clinical records [33] (Table 1 and Supplementary table S3).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations